Dois momentos da gramaticografia da língua portuguesa: Nova gramática do português contemporanêo" e gramática da língua portuguesa um estudo historiográfico - Medeiros, Sheila Regina Pinheiro Moises (2007)
This dissertation has to subject the Grammaticography Portuguese Language, focused on a historiografic vision, in two moments: the quarter part of the 20th century and the first part of the 21st century. Its aims are: a) to evidence the differences between a grammar turned to the linguistic variation, but restricted to the phrasal level, and a grammar turned to the discursive perspective; b) to verify the rupture and the continuity processes in the grammars studies, on the period of your production; c) to verify the conceptions of the grammar, of the language (understood here as a system of communication); of the language (understood as the ability to use words communicate) and of the communication presented in the grammars; d) verify the pertinence of application adequation principle proposed by Koerner (1996) to contemporaneous grammars. The research can be justified because presents a proposal of application adequation principle to moderns documents. A second justifying is the fact of it shows that the grammars studies left to be considered below the perspective of the word and the phrasal, going to be focused below the discourse/text perspective. We have as hypothesis that: a) a grammar turned to the linguistic variation, but restricted to de phrasal level, and a grammar turned to the discursive perspective has differences; b) that the books present differents conceptions of the grammar, of the language (understood here as a system of communication), of the language (understood as the ability to use words communicate) and of the communication; c) that the grammars represents rupture and continuity of the grammars studies; d) that there s a possibility of application adequation principle, proposed by Koerner (1996), to contemporaneous grammars. We working according as the parameters of the Linguistic Historiography, assuming as support the studies of the Pierre Swuiggers (1990), Konrad Koerner (1996), Cristina Altman (1997) and the work developed by Research Group Historiography Portuguese Language, of PUC-SP (2004; 2006). We based on the methodological proposal presents by Koerner (1996). Thus, we utilize the three principles proposed by this studious: the contextualization, the imanence and the adequation. The results point that the grammars are differents, because one presents a descriptive study of the standard norm in differents variants below the word and phrasal perspective, based on Sociolinguistic, and the other a standard norm description, considering the word, the phrasal and the text/discurse, and, still, based on the Linguistic Pragmatic, reflecting the epoch spirit on the grammars are produced. They also point to de possibility of application adequation principle to moderns documents, that there s continuity and rupture of the grammars studies and still that the grammars presents distinct conceptions of the grammar, of the language (understood here as a system of communication), of the language (understood as the ability to use words communicate) and of the communication